Accessing European funds through sub-measures 16.4 and 16.4A under NRDP 2014-2020 - Dan Constantin Şumovschi (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The financing of the Romanian agriculture and rural space through the SAPARD program created the technical and financial premises necessary for the process of accession to the European structures. Thus, the funds developed through the SAPARD Agency have directly contributed to the economic and social development of the rural environment, by supporting private producers, supporting agricultural associations, and financing investments made by local councils in rural areas. Subsequently, after Romania's accession to the European Union, the Paying Agency for Rural Development and Fisheries is the institution that fulfills the payment function for investment projects, financed from the European Fund for Agriculture and Rural Development. The investments made have directly contributed to economic growth and convergence of rural incomes by increasing productivity, stabilizing markets and ensuring a fair standard of living for the agricultural population. In the current budget year of the NRDP 2014-2020, according to existing analyzes, it is observed that farmers' interest in accessing grants differs from one region to another, from one sub-measure of funding to another and even from one farmer to another in the same community. Given the importance of cooperation between the actors involved in agri-food supply chains, in this paper, we conducted an analysis that seeks their interest in accessing sub-measures 16.4 and 16.4A of the NRDP 2020. In order to achieve this approach, I consulted relevant articles and specialized studies on the subject of accessing European funds for the agricultural sector and I carried out an analysis of the data provided by the Agency for the Financing of Rural Investments.
Keywords: O18; P25; R51; 330; rural financing; NRDP 2014-2020; sub-measures 16.4 and 16.4A; cooperation; agri-foodsupply chains